A Randomized Trial of Daclatasvir with Peginterferon Alfa-2B and Ribavirin for HCV Genotype 1 Infection. Issue 5 (July 2014) - Suzuki, Fumitaka; Toyota, Joji; Ikeda, Kenji; Chayama, Kazuaki; Mochida, Satoshi; Hayashi, Norio; Ishikawa, Hiroki; Miyagoshi, Hidetaka; Hu, Wenhua; McPhee, Fiona; Hughes, Eric A; Kumada, Hiromitsu
Background: Daclatasvir-containing regimens have the potential to address limitations of current regimens combining peginterferon alfa and ribavirin with first-generation protease inhibitors for treatment of chronic HCV genotype 1 infection. Methods: In this randomized, double-blind study, 27 Japanese treatment-naive patients received once-daily daclatasvir 10 mg or 60 mg or placebo, each combined with peginterferon alfa-2b/ribavirin; 18 prior null ( n =9) or partial ( n =9) responders received the same daclatasvir-containing regimens without a placebo arm. Daclatasvir recipients with protocol-defined response (HCV RNA<15 IU/ml at week 4, undetectable at week 12) were treated for 24 weeks; those without protocol-defined response and placebo recipients continued treatment to week 48. Results: Sustained virological response 24 weeks post-treatment (SVR24 ) was achieved by 66.7%, 90.0% and 62.5% of treatment-naive patients in the daclatasvir 10 mg, 60 mg and placebo groups, respectively. Prior non-responders had more frequent virological failure; 22.2% and 33.3% of daclatasvir 10 mg and 60 mg recipients, respectively, achieved SVR24 . Adverse events were similar across groups and were typical of peginterferon alfa-2b/ribavirin. Pyrexia, headache, alopecia, decreased appetite and malaise were the most common adverse events; two daclatasvir recipients discontinued due to adverse events. Conclusions: Daclatasvir 60 mg combined with peginterferon alfa-2b and ribavirin achieved a high rate of SVR24 in treatment-naive patients with HCV genotype 1 infection, with tolerability similar to that of peginterferon alfa-2b/ribavirin alone. However, regimens with greater antiviral potency are needed for prior non-responders.